BEDOUIN WOMEN STATUS UNDER THE PATRIARCHAL SYSTEM IN MIRAL AL TAHAWI’S THE TENT - Zainab Abd Ali Hammood; Lajiman Bin Janoory (Universitas Islam Sumatera Utara (UISU), 2019)
This research investigates the status of female characters under the oppressive patriarchal system of Bedouin in the novels of Miral Al Tahawi through the lens of radical feminist theory. Miral Al-Tahawi explains in her novel